Epidural Analgesia for Pain Management in Acute Pancreatitis during Pregnancy and Its Effect on Maternal and Fetal Outcome - Sandeepika Dogra; Pallavi Sharma; Sunil Pandya; Manokanth Madapu; Soumya Jagannath Mahapatra; Ankita Sethi; Nilanchali Singh (Obstetrics and Gynecology International)
Background. Acute pancreatitis (AP) during pregnancy is a rare presentation with an estimated incidence of 1 case per 1000 to 10,000 pregnancies. Severe epigastric and abdominal pain is the earliest and the most common symptom of AP, and adequate pain relief is an integral part of patient management. The aim of our study was to investigate the different pain relief modalities that are used in pregnant women with AP and the efficacy of each method used, in terms of better pain relief and maternal-fetal outcomes. Methods. This was a retrospective observational study over a period of 6 years conducted at a tertiary care hospital. Pregnant women with clinical and biochemical diagnoses of acute pancreatitis were included in the study. Patient’s history and clinical and biochemical data were collected from the medical records of the hospital. Results. A total of 12 patients were included in the study, 5 out of 12 patients had gall stones associated with AP, 2 patients had hypertriglyceridemia, and 1 each had preeclampsia and eclampsia. Epidural analgesia at the level of L1-L2 spinal level showed a reduction of VAS scores from 8 or 9 to 1 or 2, indicating excellent pain as compared to t intravenous (i/v) infusion of fentanyl or i/v boluses of injection tramadol, in whom VAS was never reduced below 3. With satisfactory results, labour analgesia and anesthesia for caesarean section was provided via the same catheter in 2 and 3 patients, respectively. Maternal and fetal outcomes were comparable in all the patients. Conclusion. AP in pregnancy, when diagnosed early and managed accordingly, leads to better maternal and fetal outcomes. Epidural analgesia was better than intravenous analgesia in terms of pain management and better recovery of acute pancreatitis patients. In these patients, labour analgesia and anesthesia for caesarean section can be provided through the same catheter, making it a potential novel modality in the treatment of acute pancreatitis in pregnancy.